Penggunaan Bahasa pada Surat Resmi BEM U KBM Unila dan Implikasinya dalam Pembelajaran - Deni Yuniardi; Mulyanto Widodo; Nurlaksana Eko Rusminto (FKIP Universitas Lampung, 2018)
The purposes of the study are to describe the use of Indonesian Correct Spelling, the effectiveness of sentences in writing the official letters of BEM U KBM Unila (the Student Executive Board - Big Family Students of Lampung University) Youth Moving Cabinet, and its implications in Indonesian learning in middle schools. This research applied descriptive method. The data collecting technique was done through documentation by collecting the official letters of BEM U KBM Unila Youth Moving Cabinet. The data sources of this research were in form of official letters of BEM U KBM Unila. Based on the results of the documentation, 50 official letters with different objectives and intentions were collected. The results of the research revealed that from the 50 letters which were the subjects of the research, the researcher found out interesting phenomena in the use of spelling and sentence effectiveness. In addition, the use of language in the official letters could be implicated in Indonesian language learning in middle schools for grade VII of odd semester.Tujuan penelitian ini adalah mendiskripsikan penggunaan Ejaan Bahasa Indonesia, keefektifan kalimat dalam penulisan surat resmi BEM U KBM Unila Kabinet Muda Bergerak, dan implikasinya dalam pembelajaran bahasa Indonesia di SMP.Metode yang digunakan adalah metode deskriptif. Teknik pengumpulan data menggunakan teknik dokumentasi, yaitu pengumpulan surat resmi BEM U KBM Unila Kabinet Muda Bergerak. Sumber data penelitian ini adalah surat resmi BEM U KBM Unila.Berdasarkan hasil dokumentasi, diperoleh 50 surat resmi dengan tujuan dan maksud yang berbeda. Hasil penelitian diketahui bahwa 50 surat resmi yang menjadi subjek penelitian ditemukan fenomena menarik dalam penggunaan ejaan dan keefektifan kalimat. Selain itu, penggunaan bahasa pada surat resmi dapat diimplikasikan dalam pembelajaran bahasa Indonesia di SMP kelas VII semester ganjil.Kata kunci :kalimat efektif, penggunaan bahasa, surat resmi